2011
DOI: 10.1039/c0jm02178d
|View full text |Cite
|
Sign up to set email alerts
|

High-performance low-temperature solution-processable ZnO thin film transistors by microwave-assisted annealing

Abstract: Oxide semiconductors afford a promising alternative to organic semiconductors and amorphous silicon materials in applications requiring transparent thin film transistors (TFTs). We synthesized an aqueous inorganic precursor by a direct dissolution of zinc hydroxide in ammonium hydroxide solution from which a dense and uniform ZnO semiconducting layer is achieved. Solution-processed ZnO-TFTs prepared at 140 C by microwave irradiation have shown enhanced device characteristics of $1.7 cm 2 V À1 s À1 mobility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 20 publications
4
150
0
Order By: Relevance
“…A large amount of work has concentrated on lowering the conversion temperature of the precursor solutions to semiconducting metal-oxide layers. Functional TFTs have been obtained at ≈200 °C or below (1) via the careful design of precursor chemistry utilizing metal alkoxides with controlled hydrolysis, [ 14,15 ] combustion process, [ 11,19 ] or the addition of oxidizing agents, [ 20 ] (2) via the use of additional energy in conversion such as various wavelengths of UV light, [ 8,15,21 ] or microwaves, [ 22 ] or (3) by employing conditions during annealing that promote effi cient precursor conversion such as ozone or vacuum. [ 6,7,20 ] After the fi rst report on inkjet-printed metal oxide layers from metal chloride precursors by Lee et al in 2007, [ 16 ] the deposition of metal-oxide semiconductor layers for TFTs has been successfully performed via several printing techniques.…”
Section: Doi: 101002/adma201502569mentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of work has concentrated on lowering the conversion temperature of the precursor solutions to semiconducting metal-oxide layers. Functional TFTs have been obtained at ≈200 °C or below (1) via the careful design of precursor chemistry utilizing metal alkoxides with controlled hydrolysis, [ 14,15 ] combustion process, [ 11,19 ] or the addition of oxidizing agents, [ 20 ] (2) via the use of additional energy in conversion such as various wavelengths of UV light, [ 8,15,21 ] or microwaves, [ 22 ] or (3) by employing conditions during annealing that promote effi cient precursor conversion such as ozone or vacuum. [ 6,7,20 ] After the fi rst report on inkjet-printed metal oxide layers from metal chloride precursors by Lee et al in 2007, [ 16 ] the deposition of metal-oxide semiconductor layers for TFTs has been successfully performed via several printing techniques.…”
Section: Doi: 101002/adma201502569mentioning
confidence: 99%
“…By combining the demonstrated process with available UV-based low-temperature annealing schemes, [ 8,15,21 ] roll-printed metal-oxide TFT devices and circuits on low-cost plastic substrates can be achieved in the future. [ 22 ] the solution was stirred at 75 °C for more than 12 h and fi ltered prior using with a 0.45 µm pore size glass fi bre fi lter. The water content of the ready ink was measured to be ≈1 wt% with Karl Fischer titration (Mettler Toledo DL37), thus indicating the presence 2.5 of crystal H 2 O per In-atom.…”
Section: Doi: 101002/adma201502569mentioning
confidence: 99%
“…In addition, the starting Zn solutions were prepared by directly dissolving Zn(OH) 2 in aqueous ammonia solutions, to produce a so-called 'impurity-free precursor'. The use of zinc hydroxide allowed for low-temperature ZnO formation, indicating rapid, low-energy kinetics of metal-amine dissociation and simple dehydration and condensation reactions to form ZnO films [61,62]. The undoped ZnO (140°C under microwave-assisted annealing) and Li doped ZnO TFTs (300°C annealing) exhibited remarkable performance: μ fe~1 .7 cm 2 /V · s and 11.45 cm 2 /V · s for undoped and Lidoped devices, respectively.…”
Section: Solution Processed Oxide Semiconductorsmentioning
confidence: 99%
“…The third process is a simple and novel 'aqueous route' for fabricating oxide TFTs at annealing temperatures below 200°C, suggested by several researchers [60][61][62]. The suggested aqueous route provides low-temperature oxideformation and good stability by restricting the hydrolysis and condensation reactions within a solution state.…”
Section: Solution Processed Oxide Semiconductorsmentioning
confidence: 99%
“…There has been encouraging progress with ZnO. Using spin-coating, Yu et al 4 achieved a mobility of 4 cm 2 /Vs for devices fabricated at 300 °C, while Xu et al 5 and Jun et al 6) have demonstrated mobilities of approximately 0.5 cm 2 /Vs using the same processing method, but with a 150 °C annealing temperature.…”
Section: Introductionmentioning
confidence: 98%